Pengaruh Strategi Dan Inovasi Produk Terhadap Keunggulan Bersaing Pada Umkm Sektor Kuliner Di Kota Denpasar - I Ketut Alit Wiguna; Nyoman Sri Manik Parasari; Desak Made Febri Purnama Sari; I Gusti Ngurah Widya Hadi Saputra (Bajang Institute, 2026)
This study aimed to analyze the effects of promotion strategy and product innovation on the competitive advantage of culinary micro, small, and medium enterprises (MSMEs) in Denpasar City. A quantitative approach with an associative research design was employed. The study population consisted of 10,766 culinary MSMEs in Denpasar City that had adopted digital technology in their business operations. A sample of 100 respondents was selected using the Slovin formula and purposive sampling technique. Primary data were collected through questionnaires and supported by secondary data obtained from relevant literature. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) with the assistance of SPSS software. The results revealed that promotion strategy had a positive and significant effect on competitive advantage, with a regression coefficient of 0.345 (p < 0.001). Product innovation also had a positive and significant effect on competitive advantage, with a regression coefficient of 0.219 (p = 0.001). Simultaneously, promotion strategy and product innovation significantly influenced competitive advantage, as indicated by an F-value of 39.676 (p < 0.001). The coefficient of determination (R²) of 0.527 indicates that both independent variables explain 52.7% of the variation in competitive advantage. These findings highlight that effective digital promotion strategies and continuous product innovation are essential for strengthening the competitiveness of culinary MSMEs in Denpasar City in the digital era.